Imagination Practices and Community-Based Learning (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2018)
Informed by my experiences in prison/university co-learning projects, this essay centres two community-based learning practices worth cultivating. First, what can happen when all participants truly prioritize what it means to build community as they address their shared project, co-discovering new ways of being and doing together, listening receptively and speaking authentically? How can project facilitators step beyond prescribed roles embedded in the charity paradigm of service-learning to invite and support egalitarian community and equity-driven decision-making from a project’s inception and development, through its unfolding and its assessment? Second, the sheer fact of a project taking place in the marginal place between two contexts gives all participants—students, faculty, community participants and hosts—the opportunity for meta-reflection on the institutional logics that construct and constrain our perspectives so acutely. What can we do, by way of project-conception and pedagogy, to open up those insights? The vantage that “the space between” provides can bring fresh understanding of the systemic forces at work in the lives of the community participants. And the university’s assumptions about itself and its place in the world can also suddenly appear strange and new, objects of scrutiny for students and community members both.